(3TeS GdYdhe hOhGA cdGe GdYQH ef Gdcdhes - (3fThGf Hf SYjO GdMejQj, CHh SYjO,J (B573 (3g` s
(3ChdgG (B:s
(3ef cJGH GdOGd , HGH GdOGd heG HYOgG ef GdMQha ai GdeVGYa , bhdg (B: (3GdCSeGA (B: (3aYd HaJM GdaGA GdOK HKdGK fbWGJ GdeWQ GdVYja Q (B: (3GdOQ Gddjf , hjbGd Gddg OQg CI Yedg hjbGd dGOQ OQg Ci dGcKQ NjQg , hCUdg ef GddHf s
(3BNQgG (B:s
(3GdRjGOI (B: (3GdCaYGd QCSg EPG cKQ ajg GdUFHGf (B: (3hGddg CYde (B[ (3GfJgi (B] (3gPG GdLRA HMeO Gddg jJdhg cJGH Gdfhf s
(3HgG fXGe GdJYbjHIs
(3fSNI YGTQIs
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B8 - (3U (B20 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B13 - (3U (B86s
Keywords: (3GddZIs